Ontogenesis of flax (Linum usitatissimum L.) somatic embryos in vitro : variation in linolenic content and the development of photosynthetic capacity - Calatroia, Manuel (2004)
Introduction: The objective of this study was to determine if there is a correlation between the increase in the content of linolenic acid of flax somatic embryos (SE) observed during their development in vitro in MS medium supplemented with 2% sucrose (Cunha and Fernandes-Ferreira, 2003) and the acquisition of photoautotrophic capacity. Linolenic acid is the main fatty acid in chloroplastidial membranes, whereas other fatty acids are predominant in other subcellular membranes and in the plasmalemma. It is also known that the presence of metabolisable substrates, such as glucose and sucrose, in plant tissue growing medium are generally inhibitory of the expression of photosynthetic phenotype. Material and Methods: Hypocotyl segment explants from in vitro grown plants were inoculated on embryogenic MS medium (Cunha and Fernandes-Ferreira, 1996) and SE plantlets were sampled, in replicates, as 5 developmental stage categories (from 1- small late-germinated to 5 - well developed ones) after 6 weeks of culture. Non-invasive photosynthetic measurements were performed with a PAM fluorometer (Walz) on 2nd or 3rd node leaves by the introduction of the optical fibre through the flask cap. Plantlets were then deep freezed and fatty acid analysis was performed as previously described (Cunha and Fernandes-Ferreira, 2003). Results and Conclusions: Results indicated that not only embryogenic and non-embryogenic flax calli evidence photosynthetic activity in media supplemented with sucrose (data not shown), but also that there was an increase in the estimated photosynthetic parameters (photosynthetic light efficiency (α) and photosynthetic capacity (Amax)) during the development of somatic flax plantlets in vitro. Photoinhibition was observed for all plantlet categories: the light intensity that causes photoinhibition increased with ontogenic development but the photoinhibition slope (β) did not differ significantly between the 5 categories. References: Cunha A, Fernandes-Ferreira M. 1996. Somatic embryogenesis, organogenesis and callus growth kinetics of flax. Plant Cell, Tiss. Org. Cult. 47: 1-8. Cunha A, Fernandes-Ferreira M. 2003. Ontogenic variations in free and esterified fatty acids during somatic embryogenesis of flax (Linum usitatissimum L.). Plant Sci. 164:863-872.